2020
DOI: 10.1163/17683084-12341759
|View full text |Cite
|
Sign up to set email alerts
|

Paisagens islâmicas na Área Metropolitana de Lisboa: (pós)colonialismo e políticas de reconhecimento

Abstract: Resumo A história do Islão e dos muçulmanos no Portugal contemporâneo está indelevelmente marcada pelas dinâmicas coloniais, mas também por processos pós-coloniais. As próprias configurações institucionais do “Islão público” na sociedade portuguesa revelam esta importância e, simultaneamente, criaram as condições para uma hierarquização de determinadas vozes e projectos entre os muçulmanos. Partindo de três pesquisas sustentadas em trabalho de campo etnográfico sobre a Associação Islâmica e Cultural da Margem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Building democracy in Portugal in the 1970s was a favorable occasion for religious diversification through post-colonial flows of Hindus and Muslims (Lourenço 2020;Mapril et al 2021). Nevertheless, the most relevant impact was in the diversification of Christian identities.…”
Section: A Revolution Without Religious Disruptionmentioning
confidence: 99%
“…Building democracy in Portugal in the 1970s was a favorable occasion for religious diversification through post-colonial flows of Hindus and Muslims (Lourenço 2020;Mapril et al 2021). Nevertheless, the most relevant impact was in the diversification of Christian identities.…”
Section: A Revolution Without Religious Disruptionmentioning
confidence: 99%
“…N. B. Weibel demonstrated that the Alsace population more easily accepted Buddhism's presence in the Alsatian religious landscape than the Islamic presence (Weibel 2020). Differently, in Portugal, a country with a Catholic majority, feelings of religiophilia are more recurrent toward Islam than toward the Universal Church of the Kingdom of God (Minga 2022;Mapril et al 2021). On the one hand, Islam is not perceived as a competing religion-its proselytizing activity is scarce.…”
Section: From State To Localmentioning
confidence: 99%
“…A historical area of Lisbon, Portugal's capital city, was the object of a mediation policy dedicated to the problem of the religious diversity concentrated there. Mapril's research made evident the role that the identification or construction of places of worship can have in the dynamics of identity remodeling-in this case, the recomposition of Bangladeshi Islam in a transnational framework (Mapril et al 2021).…”
Section: Social Uses Of Conflictmentioning
confidence: 99%